Infection of Cells with Human Cytomegalovirus during S Phase Results in a Blockade to Immediate-Early Gene Expression That Can Be Overcome by Inhibition of the Proteasome - Fortunato, Elizabeth A. (American Society for Microbiology, 2002)
Cells infected with human cytomegalovirus (HCMV) after commencing DNA replication do not initiate viral immediate-early (IE) gene expression and divide before arresting. To determine the nature of this blockade, we examined cells that were infected 24 h after release from G(0) using immunofluorescence, laser scanning cytometry, and fluorescence-activated cell sorting (FACS) analysis. Approximately 40 to 50% of the cells had 2N DNA content, became IE(+) in the first 12 h, and arrested. Most but not all of the cells with >2N DNA content did not express IE antigens until after mitosis. To define the small population of IE(+) cells that gradually accumulated within the S and G(2)/M compartments, cells were pulsed with bromodeoxyuridine (BrdU) just prior to S-phase infection and analyzed at 12 h postinfection for IE gene expression, BrdU positivity, and cell cycle position. Most of the BrdU(+) cells were IE(−) and had progressed into G(2)/M or back to G(1). The majority of the IE(+) cells in S and G(2)/M were BrdU(−). Only a few cells were IE(+) BrdU(+), and they resided in G(2)/M. Multipoint BrdU pulse-labeling revealed that, compared to cells actively synthesizing DNA at the beginning of the infection, a greater percentage of the cells that initiated DNA replication 4 h later could express IE antigens and proceed into S. Synchronization of the cells with aphidicolin also indicated that the blockade to the activation of IE gene expression was established in cells soon after initiation of DNA replication. It appears that a short-lived protein in S-phase cells may be required for IE gene expression, as it is partially restored by treatment with the proteasome inhibitor MG132.